Implementation of Learning in Early Childhood Education: A Review from the Perspective of Teachers with Non-Early Childhood Education Backgrounds - Ilmiah, Citra Faridatul Nur; Senny Weara Dienda Saputri; Reski Yulina Widiastuti (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Teachers' perceptions of early childhood education are understood as their views on early childhood education activities, which are formed from personal experiences and other influencing factors. The law on early childhood education standards also explains the qualifications of early childhood teachers. One of the PAUD institutions in Jember Regency has a majority of teachers who are non-PAUD graduates teaching. Therefore, teachers' perceptions of PAUD learning are important to understand in order to see how teachers view PAUD learning. The research was conducted using a qualitative phenomenological approach. The research data sources were 10 teachers. Data collection was carried out using interviews, observation, and documentation techniques. The results of data analysis show that teachers' understanding of PAUD learning tends to focus on teaching aspects and fulfilling tasks assigned by the school as well as the burden of the curriculum. In depth, teachers were unable to explain the stages of development, learning methods and strategies, varied learning media, and learning designs suitable for children. It can therefore be concluded that teachers' perceptions of PAUD learning are learning processes that are in line with the needs and characteristics of children. However, in practice, teachers have not implemented this in accordance with their understanding.